IMPLEMENTASI PEMBELAJARAN DARING BERBASIS MANAJEMEN MUTU PENDIDIKAN KEAGAMAAN ANAK USIA DINI (STUDI ATAS DAMPAK PENERAPAN SOCIAL DISTANCING DI TK ISLAM SE KABUPATEN GUNUNGKIDUL) - Titien Andryani S; Imam Mawardi; Imron Imron (MUADDIB Jurnal Kependidikan dan Keislaman, 2021)
This study aims to describe the implementation of online distance learning in Islamic kindergartens in Gunungkidul Regency. With research at TK IT Tunas Mulia, TK II Waladun Sholihun, TK ABA Al Mujahidin. The type of research used is descriptive qualitative with a case study approach. The results showed that the online implementation used various applications, namely google meet, zoometing, whatshap video call. The learning of religious habituation carried out is reading the Qur'an or Iqro, depositing the memorization of juz ama and daily prayers. Making daily worship journals at home. The quality of online learning is determined by the participation of parents, the quality of the material provided by the school, and the preparation of the curriculum. Constraints faced by the internet network that has not been evenly distributed and the limitations of Android ownership